Video podcast and illustrated text feedback in a web‐based formative assessment environment. Issue 2 (14th September 2017) - Letón, Emilio; Molanes‐López, Elisa M.; Luque, Manuel; Conejo, Ricardo
Abstract: It is well known that computer‐based formative assessment and timely feedback enhance effective student learning but there is still a debate about what type of feedback should be given, being the text‐based the most used feedback in practice. Although the use of video content as a learning resource has recently increased in both educational and non‐educational contexts, there is very little research on its effectiveness as assessment feedback and the existing results are contradictory. For that reason, we have combined in this work the use of a web‐based formative assessment system (Siette) where we have integrated a specific type of video podcast ("modular teaching mini‐videos": MTMs) and equivalent illustrated text. We have carried out two experiments with a twofold purpose, first to compare the effect of video feedback versus correct response feedback alone and secondly to compare the effect of video feedback versus equivalent illustrated text feedback. In the context of our research, a Statistic Course at university level, our results show, as expected, that there is a statistically significant positive effect in favor of video feedback over correct response feedback alone. Surprisingly, in contrast to our expectations, based on our context of acquisition of procedural knowledge, there is a statistically non‐significant effect of video feedback versus equivalent illustrated text feedback. From the students' satisfaction survey, there is not statistically significant differences in the overall score of the activity based on video podcast feedback or equivalent illustrated text, which is an indication that we have really obtained equivalent feedback materials.